ENHANCING STUDENTS’ SEPAKING SKILL THROUGH VIDEO BLOG (VLOG) AT SMAN 2 KALUKKU - Muhammad Ybnu Taufan (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah IX Sulawesi, 2021)
The purpose of this study was to determine the application of improving students' speaking skills through video blogs (vlogs) in speaking skills through descriptive texts in class X SMA Negeri 2 Kalukku in the academic year 2021/2022. Samples were taken in class X.IPA 1 semester II with 32 students. Furthermore, Each cycle is completed in four steps: planning, action, observation and reflection. The success indicator of 71% of students achieves the KKM score of 71. The results of the study prove that the application of improving students' speaking skills through video blogs (vlogs) can improve the quality of students' speaking. The value from cycle I to cycle III has increased. Furthermore, the results of diagnostic tests up to cycle I mean the score decreased from 5 (diagnostic test) to 8 (diagnostic test), but in this case there was also an increase. Then from cycle I to cycle III the average score for each step increased, namely 60.72 (cycle I), 79.00 (cycle II) and 90.16 (cycle III). This technique can be relied upon to develop students' speaking skills through descriptive texts. However, it must be accompanied by aspects that students must understand so that the conversation becomes a good topic